The world of Jesus : making sense of the people and places of Jesus' day - Marty, William Henry (2013)
"Bible professor teaches readers about the world Jesus lived in and the time between the Old and New Testaments"--
Keywords: Jesus Christ -- Historicity; Bible. -- History of contemporary events; Bible. -- History of contemporary events; Jews -- History -- 586 B.C.-70 A.D.; Judaism -- History -- To 70 A.D.; Jews -- History -- 168 B.C.-135 A.D.; Church history -- Primitive and early church, ca. 30-600.; Palestine -- History -- To 70 A.D.